Establishing preliminary reading fluency benchmarks for Grade 3 students in India. (5th August 2022) - Ghosh, Aditi; Misquitta, Radhika; Shenoy, Sunaina; Kotwal, Nikisha
Abstract : Background: The National Education Policy of India in 2020 indicated a goal that all children will achieve foundational literacy by Grade 3 by 2025. In line with this, the Indian government sets a target of 30 to 35 correct words per minute (cwpm) at Grade 3. However, there are no supporting data for reading fluency targets in the Indian reading literature. Similarly, international benchmarks are used in India, but there are no data examining their appropriateness for the Indian context. The purpose of this study was to develop data‐driven benchmarks for oral reading fluency (ORF) for students in Grade 3 in the Indian context. We compared both international standards and the national targets with our study's benchmarks to assess their suitability for the Indian population. Methods: This study assessed ORF in English for Grade 3 students from three schools following three different curricula in India. The primary tool employed was Fluency and Benchmarking for Literacy in Education (FABLe), a digital curriculum‐based measurement tool developed specifically for the Indian context. Students were assessed at the beginning and end of the academic year. Results: The performance data collected using FABLe when compared with the international benchmarks were significantly skewed, especially for the end of the year. The national Grade 3 fluency target was found to be even lower than the 5th percentile at the end of the year. Conclusion: Employing international tools and benchmarks may lead to an overidentification of the number of students that need support, and the current Indian government target may lead to an under‐identification of the same population of students. This study fills an important research gap by providing schools with a Grade 3 ORF measure developed for the Indian context. The results should be considered a preliminary benchmark in Grade 3 and be used to inform literacy practices. Highlights: What is already known about this topic The Government of India has declared a Grade 3 target of 30 to 35 correct words read per minute, which is aligned to the National Education Policy 2020 goal of achieving foundational literacy for all students by Grade 3. International benchmarks are being employed in India, but there are no data to indicate their suitability for the Indian context. The available Indian benchmarks are based on limited data from Grade 1 and 2 students and from other developing countries. What this paper adds This study presents preliminary data‐driven benchmarks for English oral reading fluency (ORF) at the beginning and end of Grade 3 in the Indian context. The study compares student performance with respect to the international benchmarks as well as with the Indian national target, highlighting the need to develop specific benchmarks for the Indian population. Implications for theory, policy or practice Currently, there are no benchmarks available for the Indian context. Policy‐makers can use FABLe benchmarks to set more realistic reading targets. International benchmarks may tend to overidentify students, and the national targets may tend to under‐identify students needing support. Indian educators can make use of FABLe benchmarks to more accurately identify students in need of intervention. Using the benchmarks, schools and educators can develop reading profiles of students to guide data‐driven instruction and monitor student progress.